Metode Ilmu Sebagai Sarana Memahami Ilmu Pengetahuan Dalam Meraih Kebijaksanaan - Syahriani Siregar; Yatin Mulyono (Departement of Mathematics Education, 2024)
Understanding science is essential in achieving wisdom. Science provides a solid foundation of knowledge and a deep understanding of the world around us. The scientific method is an important tool for understanding science. Scientific methods help us to think critically, analyze information, and draw logical conclusions. In this research, the author will discuss the role of scientific methods as a means of understanding science in achieving wisdom. The author will explain several commonly used scientific methods, such as deductive, inductive and experimental methods. The author will also discuss how scientific methods can help us think critically, analyze information, and draw logical conclusions.